EDUKASI PENDIDIKAN KESETARAAN GENDER UNTUK MENCIPTAKAN RELASI SEHAT DAN HARMONIS - Antonius Ian Bayu Setiawan; A. Setyandari; Prias Hayu Purbaning Tyas (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
The cases of violence against women requires attention from many parties, especially the need for assistance in understanding gender equality. Equal relations will provide men and women with the same opportunities and rights, so that women are not subordinated in the household. Unequal power relations often become problems in families and couple relationships, which can lead to gender-based violence. The purpose of this community service activity is to provide an understanding of gender equality education to create healthy and harmonious relationships. The implementation method in this activity uses Participatory Action Research (PAR) with four activity steps, including the exploration phase, the planning phase, the implementation phase, and the reflection and evaluation phase. The number of participants in this activity was 28 people consisting of groups of mothers and teenagers who were divided into three different classes to receive different interventions. The intervention used a group guidance model, which emphasizes group dynamics. The result of this activity is an increased understanding of gender equality after the intervention. The intervention contributes to society being able to behave in a gender-just manner, so that the number of cases of violence against women can be addressed.